Influence of weather conditions on variability of breeding valuable characteristics of winter rye varieties in Kirov region - N. A. Nabatova; E. I. Utkina; E. A. Psareva (Аграрная наука Евро-Северо-Востока, 2023)
Long-term results of the research on the influence of weather conditions on the formation of economically biological and technological characteristics of winter rye varieties are valuable for further use in practical breeding, as well as in solving the problem of realizing their biological potential in a wide range of soil and climatic factors.   The aim of the research was to evaluate the influence of weather conditions on the variability of yield, economically biological characteristics and baking properties of 10 winter rye varieties of different geographical origin for the subsequent creation of varieties adapted to the conditions of Kirov region.   As a result of eight years of research (2015-2022), the variability of 19 biological and technological characters was analyzed in different weather and climatic conditions (index of environmental conditions from +1.44 to -1.39). The highly stable characteristics were grain nature, ear density and relative ear productivity (CV = 1-8 %). The least stable traits were yield and winter hardiness (CV = 75-89 %). Analysis of variability of characteristics by varieties revealed the most adapted to changes in weather conditions varieties - Rushnik, Falenskaya 4, Flora, Alisa (from 2-3 to 38-42 %). The principal component method with visualization on a biplot chart was used to assess the influence of characteristics on yield formation. It was revealed that the yield was more dependent on the weight of 1000 grains, snow mold damage, winter hardiness, resistance to lodging, length and weight of the ear, number of spikelets and grains in the ear, weight of grain per ear and plant, relative productivity of the ear. These traits determined 65.9 % of yield variability. The second biplot chart allowed to identify the most stable varieties for 8 years of study – Rushnik, Falenskaya 4, Flora and Alisa. It was found that the variety of winter rye Alisa realizes its yield potential both in years with optimal conditions of vegetation and in conditions of excessive moisture, but differs from the varieties Falenskaya 4, Flora and Rushnik in high ear productivity and can be used as a source material for breeding.